The Invisibility of Women's Organizations in Decision Making Process and Governance in Nigeria - Afolabi, Comfort Yemisi (Frontiers in Sociology, 2019)
The most fascinating development in politics has been the increase in women’s political participation globally. Women are becoming more engaged in variety of institutional decision making processes and Africa appears to be leading in women’s parliamentary representation. Since the re-birth of democracy in Nigeria in 1999, women have tried to gain access to decision making positions by contesting at various political levels and representation of women’s organizations on various policy debates have increased at local and national levels. However, their efforts appear not to be greeted with much gains as the result seems not very encouraging. What is problematic is whether the representation of women’s organization in democracy and decision making in Nigeria is descriptive or substantive. Even when women’s organizations are represented in the decision making arena, it appears that their influence were not much felt. This paper will investigate the invisibility or otherwise of women’s organizations in decision making process and governance in Nigeria, its implications and Challenges. The study employed descriptive survey research design. Purposive sampling technique was used to select the six South Western States in Nigeria and 150 respondents from women’s organizations who were willing to participate in the study. A self-designed instrument was used to gather data for the study. The research instrument was validated and texted for its level of reliability, using Pearson Product Moment Correlation Analysis for its co-efficient. Nine research questions were generated to guide the study. The data obtained were analyzed using descriptive analysis, frequency counts and percentages. The findings revealed that the roles played by women’s organizations in decision making arena was significant but not visible and unappreciated. It was therefore, recommended that women’s organizations should do all they can to be more active in governance and encourage more women to be fully involved in decision making process in Nigeria for national development. Keywords: Women’s organizations, decision making, invisibility, descriptive, substantive representation.